High mass flux air atomized spray with subcooled water: A novel methodology to enhance the heat transfer rate in film boiling regime. (May 2018) - Panda, A.; Pati, A.R.; Pradhan, S.; Saha, B.; Kumar, A.; Mohapatra, S.S.
Highlights: Heat removal rate is enhanced and unaltered surface morphology is achieved by using subcooled water as a coolant. The percentages of increment in qIHF and qAHF (MW/m 2 ) of WT at 15 °C are found to be 60 and 4, respectively. The maximum obtained cooling rate is 157 °C/s, which lies in Ultrafast cooling regime. Abstract: The main challenging tasks in the successful implementation of ultrafast cooling in the manufacturing process are significant reduction of Leidenfrost effect and achievement of unaltered surface morphology. The literature does not reveal any methodology depicting the aforesaid two characteristics and therefore, in the current work, an attempt has been made to develop a cooling process describing the above mentioned characteristics. In the proposed methodology, by using subcooled water as a coolant in case of high mass flux air atomized spray, the heat transfer rate is significantly enhanced without altering the surface morphology. The high mass flux subcooled water atomized spray augments the heat transfer rate by reducing the stability of the vapour film separating the coolant from the hot plate. The cooling ability of the subcooled water atomized spray is compared with the coolants, which depict significant enhancement, and the comparison confirms the suitability of the current process for the fast cooling operation. For the experimental investigation, air atomized spray cooling was conducted at 1000 °C initial surface temperature on a 6 mm thick AISI 304 steel plate by using subcooled water as a coolant. The surface heat flux and surface temperatures are predicted by using the solution of inverse heat conduction problem (IHCP). For the understanding of heat transfer mechanism, the thermal properties, physical properties and spray properties at different conditions of air-atomized spray were analysed. The percentage of enhancement in initial heat flux (qIHF ) is found to be almost 60% of water temperature at 15 °C and this shows the appropriateness of the process for the fast cooling operations. The heat transfer analysis illustrates that the cooling rate achieved for water temperature of 15 °C is found to be almost three times of that corresponding to 50 °C. In addition to the above, the comparison of the morphologies between the heat-treated and the untreated substrate corroborates zero deposition of coolant after cooling. The effects of air flow rate and spray impingement density on the cooling rate are investigated. With the increasing airflow rate up to 30 m 3 /h, the heat transfer rate rises and thereafter, further increment declines the heat transfer rate.